LITERARY ECOCRITICISM IN THE ORAL TRADITIONS OF CIAMIS REGENCY: CULTURAL CONSERVATION AND ENVIRONMENTAL VALUES IN THE KADATUAN GALUH PAKUAN COMMUNITY: CULTURAL CONSERVATION AND ENVIRONMENTAL VALUES IN THE KADATUAN GALUH PAKUAN COMMUNITY - Sri Mulyani; Andri Noviadi; Hendaryan; Heryanto Gunawan; Tegar Rizki Barkah; Novita Aprilia; Algysna Komara (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to explore and analyze environmental (ecological)values in the oral traditions of the Ciamis community using a literaryecocriticism approach. The research focuses on how folklore, songs(tembang), mantras, and proverbs (petatah-petitih) are inherited tomaintain the balance between humans and nature. Ciamis Regencypossesses a rich variety of oral traditions, which function not only asentertainment but also contain ecological messages reflecting thecommunity's worldview. However, modern lifestyle shifts havecaused these values to be neglected. Employing a qualitativedescriptive method, data were collected from key cultural sitesincluding Kampung Kuta, Panjalu, Rancah, and Karangkamulyan.The results indicate that Ciamis oral traditions are laden withecological messages, categorized into four themes: (1) Forestconservation through the "Leuweung Larangan" myth; (2) Waterglorification through the "Nyangku" ceremony; (3) Agricultural ethicsin "Nyi Sri Pohaci" praises; and (4) Human-animal relationships in the"Ciung Wanara" legend. These traditions serve as vital resources forbuilding environmental awareness and strengthening communitycharacter.